Neutropenia Is Not Associated With the Outcomes in Patients With Kawasaki Disease - Tang, Yunjia; Gang, Miao; Qian, Weiguo; Ma, Jin; Xu, Qiuqin; Lv, Haitao (Frontiers in Pediatrics, 2021)
Objective: To investigate the outcomes of coronary artery lesions (CALs) and intravenous immunoglobulin (IVIG) resistance in patients with and without neutropenia during the disease course and to explore the relationships between Δ absolute neutrophils count (ΔANC) and the outcomes. Methods: We retrospectively reviewed the medical records of patients hospitalized in Children’s Hospital of Soochow University with a main diagnosis of KD during Jan 2019 and Dec 2019. 1:4 propensity score matching was carried out to adjust the baseline characteristics. Smoothed plots and threshold effect analyses were performed to reveal the relationships between ΔANC and the outcomes. Results: Of the 438 patients enrolled, 75 (17.1%) were neutropenia cases and 363 (82.9%) were non-neutropenia cases. Patients with neutropenia were younger, had lower levels of initial ANC, white blood cell (WBC) count and C-reactive protein (CRP). Propensity score matching included 75 neutropenia and 247 non-neutropenia patients. No significant difference was found between neutropenia and non-neutropenia groups regarding CALs, coronary artery aneurysms, irregular coronary lumen, IVIG resistance and days of fever duration. There was a nonlinear relationship between ΔANC and IVIG resistance. However, threshold effect analysis showed the incidence of IVIG resistance decreased with increasing ΔANC before the turning point (ΔANC = 1.6) (OR = 0.65, 95% CI = 0.50-0.8,4 P = 0.001). On the other hand, there was a linear relationship between ΔANC and CALs, even after adjusting the confounders (OR = 1.06, 95% CI = 1.02-1.11, P = 0.008). Conclusions: Neutropenia after IVIG was not exactly associated with the outcomes. However, ΔANC counted regarding CALs and IVIG resistance.